Analisis Daya Saing Industri Keuangan Syariah Di Provinsi Gorontalo : Peluang & Tantangan - Kurniati, Kurniati; Latif, Abdul (JSAP : Journal Syariah and Accounting Public, 2025)
Abstract:Abstract. Research in the field of Islamic finance industry is needed to determine the level of public interest in the development of Islamic finance. In addition, in competition with the non-Islamic financial industry, this study can provide insight into the factors that influence people's decisions to choose Islamic financial services, as well as effective marketing strategies. This is important to increase market share, especially Islamic banking which is still relatively small compared to non-Islamic banking. This study aims to analyze the Competitiveness of the Islamic Finance Industry in Gorontalo Province. This type of research is qualitative research. The analysis used is secondary data analysis presented descriptively. This research was conducted by means of a literature study/literature review taken from various existing sources in the form of data or published documents from Bank Indonesia, journals, books, articles, and other reading findings related to the research topic. The results of this study show the Development of the Competitiveness of the Islamic Finance Industry in Gorontalo by Carrying out an analysis of the development of Islamic banks in Gorontalo. Abstrak.Penelitian di bidang industri Keuangan syariah diperlukan untuk mengetahui besarnya minat masyarakat terhadap perkembangan keuangan syariah. Selain itu, dalam persaingan dengan industri keuangan non syariah, penelitian ini dapat memberikan wawasan tentang faktor-faktor yang mempengaruhi keputusan masyarakat untuk memilih layanan keuangan syariah, serta strategi pemasaran yang efektif. Ini penting untuk meningkatkan pangsa pasar khususnya perbankan syariah yang masih relatif kecil dibanding dengan perbankan non-syariah. Penelitian ini bertujuan untuk menganalsis Daya Saing Industri keuangan Syariah di Provinsi Gorontalo. Jenis penelitian ini adalah penelitian kualitatif. Adapun analisis yang digunakan yaitu analisis data skunder yang disajikan secara deskriptif. Penelitian ini dilakukan dengan cara studi kepustakaan/ literature review yang di ambil dari berbagai sumber yang ada berupa data atau dokumen publish Bank Indonesia, jurnal, buku, artikel, serta temuan baca lainnya yang berkaitan dengan topik penelitian. Hasil penelitian ini menunjukkan Perkembangan Daya Saing Industri Keuangan Syariah di Gorontalo Dengan Melaksanakan analisis perkembangan bank syariah di Gorontalo.Kata kunci: Industri keuangan syariah di Gorontalo, Industri Syariah , Perbankan Syariah